2002
DOI: 10.1038/nsb876
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-binding mode of vWF-A3 domain determined by a transferred cross-saturation experiment

Abstract: The nature of the supramolecular complex between fibrillar collagen and collagen-binding proteins (CBPs) has hindered detailed X-ray and NMR analyses of the ligand-recognition mechanism at atomic resolution because of the lack of appropriate approaches for studying large heterogeneous supramolecular complexes. Recently, we proposed an NMR method, termed transferred cross-saturation (TCS), that enables the rigorous identification of contact residues in a huge protein complex. Here we used TCS to study the supra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 31 publications
1
75
0
Order By: Relevance
“…Apparently, the introduction of a much larger histidine side chain at this position blocks the binding of 82D6A3 and A3 by steric hindrance. However, Nishida et al (32) reported an important decrease in collagen binding of the P982A mutant, but they used isolated A3-domain mutants, whereas we expressed the full-length VWF protein. Apart from the P981H mutation, mutation of Arg 963 , Asp 1009 , Arg 1016 , Ser 1020 , Met 1022 , and His 1023 to alanine also affected 82D6A3 binding with R963A, R1016A, S1020A, and H1023A previously reported to result in a reduced collagen binding (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, the introduction of a much larger histidine side chain at this position blocks the binding of 82D6A3 and A3 by steric hindrance. However, Nishida et al (32) reported an important decrease in collagen binding of the P982A mutant, but they used isolated A3-domain mutants, whereas we expressed the full-length VWF protein. Apart from the P981H mutation, mutation of Arg 963 , Asp 1009 , Arg 1016 , Ser 1020 , Met 1022 , and His 1023 to alanine also affected 82D6A3 binding with R963A, R1016A, S1020A, and H1023A previously reported to result in a reduced collagen binding (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…After submission of this manuscript, Nishida et al (35) reported mapping of the collagen-binding site of the VWF-A3 domain using a novel NMR technique. Their findings with regard to the location of the binding site and the orientation of a bound collagen triple helix are in complete agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…The collagen-binding A3 domain of VWF has been crystallized and its collagen binding site mapped by NMR, antibody blocking and mutagenesis experiments (35)(36)(37)(38). The collagenbinding site delineated by these studies is a shallow groove, with no obvious Phe pocket.…”
Section: Prediction Of Sparc-binding Sites In Collagens I-ivmentioning
confidence: 99%